2007
DOI: 10.1371/journal.pbio.0050138
|View full text |Cite
|
Sign up to set email alerts
|

Mental Training Affects Distribution of Limited Brain Resources

Abstract: The information processing capacity of the human mind is limited, as is evidenced by the so-called “attentional-blink” deficit: When two targets (T1 and T2) embedded in a rapid stream of events are presented in close temporal proximity, the second target is often not seen. This deficit is believed to result from competition between the two targets for limited attentional resources. Here we show, using performance in an attentional-blink task and scalp-recorded brain potentials, that meditation, or mental train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

42
586
10
22

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 628 publications
(660 citation statements)
references
References 31 publications
(47 reference statements)
42
586
10
22
Order By: Relevance
“…were not meditating during AB task performance (Slagter et al, 2007(Slagter et al, , 2009van Leeuwen et al, 2009), and extends these findings by showing that different meditative states may differentially affect the AB.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…were not meditating during AB task performance (Slagter et al, 2007(Slagter et al, , 2009van Leeuwen et al, 2009), and extends these findings by showing that different meditative states may differentially affect the AB.…”
Section: Discussionmentioning
confidence: 58%
“…Based on these descriptions and the previous study by Slagter et al (2007Slagter et al ( , 2009, we predicted that OM meditation-with its emphasis on non-reactively monitoring the content of experience from moment-to-moment, without focusing on any explicit object-would be associated with a smaller AB than FA meditation due to reduced attentional capture by T1 during OM meditation. In contrast, we predicted that T1 accuracy, the simple ability to perceive stimuli, would not be affected differentially by OM vs. FA, because even though Slagter et al…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…In a longitudinal study, Slagter et al (2007) found a reduced attentional-blink deficit after a 3-month period of intensive Vipassana meditation. Newberg et al (2001) reported regional cerebral blood flow (rCBF) findings concerning a thalamic laterality index difference between Tibetan Buddhist meditators and controls at rest, with meditators showing relative higher rCBF right than controls.…”
Section: Introductionmentioning
confidence: 95%
“…Recently, several studies have provided evidence that following targeted interventions, and with the appropriate training, at least some cognitive functions, including fluid intelligence (Feuerstein, 1980;Jaeggi, Buschkuehl, Jonides, and Perrig, 2008), attentional states (Slagter, Lutz, Greischar, Francis, Nieuwenhuis, Davis, and Davidson, 2007;Tang and Posner, 2009) and working memory capacity (Klingberg, Fernell, Olesen, Johnson, Gustafsson, Dahlstrom, Gillberg, Forssberg, and Westerberg, 2005).…”
Section: Introductionmentioning
confidence: 99%